Molecular cloning, expression, and characterization of endoglucanase genes from Fibrobacter succinogenes AR1. - Cavicchioli, R (1991)
A cosmid gene library was constructed in Escherichia coli from genomic DNA isolated from the ruminal anaerobe Fibrobacter succinogenes AR1. Clones were screened on carboxymethyl cellulose, and 8 colonies that produced large clearing zones and 25 colonies that produced small clearing zones were identified. Southern blot hybridization revealed the existence of at least three separate genes encoding cellulase activity. pRC093, which is representative of cosmid clones that produce large clearing zones, was subcloned in pGem-1, and the resulting hybrid pRCEH directed synthesis of endoglucanase activity localized on a 2.1-kb EcoRI-HindIII insert. Activity was expressed from this fragment when it was cloned in both orientations in pGem-1 and pGem-2, indicating that F. succinogenes promoters functioned successfully in E. coli. A high level of endoglucanase activity was detected on acid-swollen cellulose, ball-milled cellulose, and carboxymethyl cellulose; and a moderate level was detected on filter paper, Avicel, lichenan, and xylan. Most activity (80%) was localized in the periplasm of E. coli, with low but significant levels (16%) being detected in the extracellular medium. The periplasmic endoglucanase had an estimated molecular weight of 46,500, had an optimum temperature of 39 degrees C, and exhibited activity over a broad pH range, with a maximum at pH 5.0.